2022
DOI: 10.1101/2022.01.14.476317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural and thermodynamic analyses of the β-to-α transformation in RfaH reveal principles of fold-switching proteins

Abstract: The two-domain protein RfaH, a paralog of the universally conserved NusG/Spt5 transcription factors, is regulated by autoinhibition coupled to the reversible conformational switch of its 60- residue C-terminal KOW domain between an α-hairpin and a β-barrel. In contrast, NusG/Spt5-KOW domains only occur in the β-barrel state. To understand the principles underlying the drastic fold switch in RfaH, we elucidated the thermodynamic stability and the structural dynamics of two RfaH- and four NusG/Spt5-KOW domains b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Chemical exchange saturation transfer (CEST) experiments demonstrated that another fold‐switching protein, the C‐terminal domain of RfaH (discussed in the following section), populates its folded state at 95% and a partially folded state with residual secondary structure corresponding to the fold‐switched state at 5%. [ 59 ] In both cases, the folded ensembles of these proteins populate both distinctly folded states, explaining how environmental triggers can switch the proteins from one energetically favorable conformation to the other.…”
Section: Evidence For Fluid Fold Spacementioning
confidence: 99%
See 4 more Smart Citations
“…Chemical exchange saturation transfer (CEST) experiments demonstrated that another fold‐switching protein, the C‐terminal domain of RfaH (discussed in the following section), populates its folded state at 95% and a partially folded state with residual secondary structure corresponding to the fold‐switched state at 5%. [ 59 ] In both cases, the folded ensembles of these proteins populate both distinctly folded states, explaining how environmental triggers can switch the proteins from one energetically favorable conformation to the other.…”
Section: Evidence For Fluid Fold Spacementioning
confidence: 99%
“…[ 98 ] Although PTMs have not been shown to switch a protein's structure from one stable fold to another, an observation of an intrinsically disordered protein (IDP) suggests that such transitions may be possible for fold‐switching proteins, which tend to have less stable ground states than canonical globular proteins. [ 31,59 ] Specifically, extensive NMR analysis revealed that multi‐site phosphorylation induces the neural IDP 4E‐BP2 to fold. [ 99 ] This study demonstrates that post‐translational modifications can dramatically shift the relative populations within a protein's structural ensemble.…”
Section: Implications Of Fluid Fold Spacementioning
confidence: 99%
See 3 more Smart Citations